Health care professionals' attitudes regarding palliative care for patients with chronic heart failure: an interview study. Issue 1 (December 2016) - Ziehm, Jeanette; Farin, Erik; Seibel, Katharina; Becker, Gerhild; Köberich, Stefan
Abstract Background Even though struggling with similar symptom burden, patients with chronic heart failure (CHF) receive less palliative care than patients suffering from malignant diseases. Researchers have found that this might be related to lack of knowledge about palliative care, insufficient interprofessional communication as well as the cyclic course of disease which makes accurate prognosis difficult. However, research findings have shown that patients with CHF benefit from palliative care. As there are no studies for the German health care system this study aimed to assess health care professionals' attitudes regarding palliative care of CHF patients in order to identify barriers and facilitators for this patient group and hence to develop recommendations for improvement of CHF patients' access to palliative care in Germany. Method Problem-centered interviews with 23 health care professionals involved in care of CHF patients (nurses: hospital, outpatient, heart failure, PC; physicians: hospital and resident cardiologists, general practitioners) were conducted and analysed according to Mayring's qualitative content analysis. Results Most interviewees perceived a need for palliative care for CHF patients. Regarding barriers patients', public's, and professionals' lack of knowledge of palliative care and CHF; shortcomings in communication and cooperation of different professional groups; inability of cardiology to accept medical limits; difficult prognosis of course of disease; and patients' concerns regarding palliative care were described. Different attitudes regarding appropriate time of initiation of palliative care for CHF patients (late vs. early) were found. Furthermore, better communication and closer cooperation between different professional groups and medical disciplines as well as better education about palliative care and CHF for professionals, patients, and public were cited. Conclusions Palliative care for CHF patients is a neglected topic in both practice and research and should receive more attention. Barriers to palliative care for CHF patients might be overcome by: better education for the public, patients, and professionals, closer cooperation between the different professional groups involved as well as development of a joint agreement regarding the appropriate time to administer palliative care to CHF patients. Trial registration DRKS00007119 .